TWO-DIMENSIONAL PHYSICAL MODEL OF CURVED CCM CONTINUOUSLY CAST SLAB FLATTENING - Polyeshchuk, Valentin; Brovkin, Vladimir; Radchenko, Yuriy; Vorobiova, Liliia (Scientific Journal "Metallurgy", 2021)
Linear configurations of the deformed state of a continuously cast ingot at its movementalong a process channel of curved continuous-casting machines (CCMs) were analyzed. Theillegitimacy of the majority of assumptions applied in the development of the physical model ofdeformation for a solidified crust of an ingot was demonstrated. The peculiarities of deformedstate development in the solid ingot crust in all sections of the curved part of the process channelwere reviewed. A two-dimensional configuration of deformed ingot crust state at flattening isproposed. The configuration is based on basic positions of continuous medium mechanics. It isshown that the two-dimensional configuration adequately shows the peculiarities of the deformedingot crust state in the sections of maximum deformation at flattening. The physicalmodel considers two surface crusts of a sufficiently wide slab that are separated by a liquidcore. The deformation of the crusts is determined by the configuration of the CCM processchannel. Two cases are analyzed in the paper: with a straight mould and with a curved mould.Formulas for calculating the ultimate deformation are given for these two cases. The locationsof the sections of maximum tensile deformation caused by flattening at slab movement alongthe process channel of curved CCMs have been determined. Two critical sections of possibleingot fracture have been identified in a CCM with a straight mould. One critical section has beenidentified in a CCM with a curved mould. The results of work can be applied to develop the engineeringpractice of thermal and mechanical design of the process channel of a curved CCM.